Tunisia Economic Monitor, Summer 2022 : Navigating the Crisis during Uncertain Times - World Bank (Washington, DC, 2022)
The war in Ukraine and rising commodity prices have exacerbated the vulnerabilities of the Tunisian economy in the first months of 2022. The impact of the war began to be felt as the trade deficit widened by 56 percent in the first six months of 2022 reaching 8.1 percent of GDP. Lower oil and gas production and increased demand for energy and agricultural products have exacerbated the vulnerability of the trade balance to the vagaries of international markets. With a challenging global environment, the economic recovery appears weaker than previously forecast.